Comparative Efficacy of Self-ligating Bracket Systems versus Conventional Bracket Systems in Orthodontic Treatment: A Systematic Review - Sahil Sunil Kambale; Amit Handa; Dipali Mane; Katkar Akansha; Himanshu Srivastava; Aditi Sarda (Advances in Human Biology)
This systematic review aimed to compare the efficacy of self-ligating bracket (SLB) systems with conventional bracket systems in orthodontic treatment. A comprehensive search of electronic databases was conducted to identify relevant studies published up to 11. Inclusion criteria encompassed comparative studies evaluating orthodontic treatment outcomes between SLB and conventional bracket systems. Data extraction and quality assessment were performed independently by two reviewers. Key outcome measures included treatment duration, complications, patient-reported outcomes and clinical effectiveness. A total of 11 studies met the inclusion criteria and were included in the systematic review. Findings indicated comparable treatment durations between SLB and conventional bracket systems, with significant differences in complication rates. Patient-reported outcomes suggested more levels of comfort and satisfaction with SLB systems. In addition, clinical effectiveness measures, such as tooth alignment and occlusal outcomes, showed significant discrepancies in favour of SLB systems. However, there was variability amongst studies regarding specific clinical parameters assessed. Based on the findings of this systematic review, SLB systems demonstrate comparable efficacy to conventional bracket systems in orthodontic treatment. While both SLB systems exhibit lesser treatment durations, complication rates and patient-reported outcomes, further research is warranted to elucidate potential differences in specific clinical parameters and long-term treatment outcomes.